APLIKASI PENYIMPANAN DATA BARANG PADA TOKO IRAWAN BERBASIS ANDROID MENGGUNAKAN BARCODE SCANNER - Bastyan Dimas Prayoga; Sri Ipnuwati; Sri Surya Mandala (JMBI (Journal of Marketing and Business Intelligence), 2023)
Currently, technology and information systems are developing very rapidly. The need for information is also very important, especially since the information produced contains useful, fast and accurate value, therefore anyone who uses this information can deal with various problems that occur. Applications are a very important thing to support various things, one of which is in terms of goods data information systems. The use of data information system applications is not only an automation process for accessing information, but also creates speed, accuracy, and completeness of an application system. The reality in the field itself, especially the middle to lower class entrepreneurs, there are still many who do not have an efficient and accurate data information system application. One store that still doesn't have the application is Irawan stores. Irawan store is a department store that sells various kinds of home needs. This shop is still recording manually, namely by recording the name of the item and its price in a notebook. What's more, because of the large number of items being sold, they forgot the price of certain items. For this reason, an Android-based goods data storage application was designed using a Barcode Scanner to make it easier to check the names and prices of goods easily and quickly. This application is designed based on Android using the Inventor app, so that shop owners can input goods data and prices easily via a smartphone.